Ultrasound-Mediated One-Pot Synthesis of 7-Methyl-Substituted Pyrido[4,3-d]pyrimidine Scaffolds by a Catalyst-Free Protocol - Sarmah, Manas M.; Prajapati, Dipak (Synlett, 2015)
A one-pot and catalyst-free protocol for the construction of 7-methyl-substituted pyrido[4,3-d]pyrimidine derivatives from ethanolic solution of 6-[2-(dimethylamino)prop-1-enyl]-1,3-dimethyluracil, aromatic aldehyde, and ammonium acetate is described under both ultrasound and thermal conditions. The ultrasound methodology is clean and the desired products are obtained with good yields in short time.
Keywords: multicomponent reactions; aza-Diels–Alder; one-pot; pyrido[4,3-d]pyrimidine; ultrasound-assisted organic synthesis; green chemistry